2001
DOI: 10.1063/1.1357833
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of spin dependent tunneling junctions with CoFeHfO as free layers

Abstract: Spin-dependent tunneling (SDT) structures of Ta–Cu–Ta–CoFeHfO–Al2O3–FeCo–CrPtMn have been deposited by rf diode sputtering. The junctions have been fabricated using photolithographic techniques. A junction magnetoresistive ratio as high as 34% has been obtained after annealing the junctions at 250 °C for 1 h. The junctions have a typical bias voltage of 475 mV at half-maximum magnetoresistance values. The resistance–area–product is about 1 MΩ μm2, and the dc breakdown voltage is about 1.5 V. AlN has also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…A magnetic field of 4 kA/m was applied during the magnetic layer deposition to induce the easy axis. Annealing was done in forming gas at a temperature of 250 C for 1 hour with an applied field of 318 kA/m to align the pinning layer structure [11]. The antiferromagnetic (AFM) CrMnPt layer for pinning is at the top.…”
Section: Methodsmentioning
confidence: 99%
“…A magnetic field of 4 kA/m was applied during the magnetic layer deposition to induce the easy axis. Annealing was done in forming gas at a temperature of 250 C for 1 hour with an applied field of 318 kA/m to align the pinning layer structure [11]. The antiferromagnetic (AFM) CrMnPt layer for pinning is at the top.…”
Section: Methodsmentioning
confidence: 99%
“…Hayakawa et al [10] first reported that Fe-M-O (M = Hf, Zr) magnetic films possessed a good magnetic softness owing to their nanostructure which consisted of ferromagnetic bcc nanocrystals (∼10 nm in size) embedded in an amorphous matrix containing large amounts of M and O elements. Soon after this work, several attempts were made to improve the high-frequency performance of these films [11][12][13][14][15][16][17][18][19]. It was found that the addition of Co to Fe-Hf-O films led to a significant improvement in the high-frequency magnetic response, mainly due to an increase in the crystalline anisotropy of the nanograins.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the recent findings of new magnetic oxide thin films are of practical importance in high-frequency applications because these materials can show a good highfrequency performance into the gigahertz range owing to their resistivity, which is approximately ten times higher than that of conventional magnetic alloy films [6,7,[10][11][12][13][14][15][16][17][18][19]. Hayakawa et al [10] first reported that Fe-M-O (M = Hf, Zr) magnetic films possessed a good magnetic softness owing to their nanostructure which consisted of ferromagnetic bcc nanocrystals (∼10 nm in size) embedded in an amorphous matrix containing large amounts of M and O elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations